Determining intention to buy air e-tickets in Malaysia - Kwee-Fah, Lee; Haque, Ahasanul; Maulan, Suharni; Abdullah, Kalthom (Growing Science, 2019)
Struggling airlines can save cost and improve profits by selling tickets online. While global sales of air e-tickets have grown over time, they are mostly from advanced nations. In developing markets like Malaysia, e-ticket sales are substantially lower. Hence, this study sets out to examine the factors that determine consumers’ intentions to buy air e-tickets. The factors include the disadvantage and advantage of buying air e-tickets, represented by perceived risk and perceived usefulness, respectively. The results show that Malaysian consumers’ perceptions of risk outweigh the perceived usefulness of e-ticketing, and negatively affect intentions to buy air e-tickets. Perceived risk also has a negative effect on perceived usefulness, making usefulness insignificant to buying intention online. These findings imply that for Malaysian consumers, perceived risk far outweighs perceived usefulness where intention to buy air e-tickets is concerned. © 2019 by the authors; licensee Growing Science, Canada.